Citrus Consumption and Risk of Melanoma: A Dose-Response Meta-Analysis of Prospective Cohort Studies - Fang, Xuexian; Han, Dan; Yang, Jun; Li, Fulun; Sui, Xinbing (Frontiers in Nutrition, 2022)
Background Epidemiological studies of citrus consumption in relation to melanoma risk have yielded conflicting results. This meta-analysis was performed to investigate the dose-response association between citrus consumption and risk of melanoma. Methods Relevant prospective cohort studies were identified by searching PubMed, Embase, Scopus, and Web of Science databases up to February 28th, 2022. Results from individual studies were pooled using a random-effects model. Results Five prospective studies, with 8,836 melanoma cases and 977,558 participants, were included in the meta-analysis. A significantly increased risk of melanoma was associated with the highest categories of either total citrus products (RR: 1.20; 95% CI: 1.01–1.42) or citrus fruit consumption (1.15; 1.04–1.28), but consumption of citrus juice was not associated with melanoma risk (1.08; 0.97–1.21). The dose-response analyses revealed that for per 1 serving/day increase in total citrus or citrus fruit consumption, the risk of melanoma increased by 9 and 12%, respectively. An inverted U-shaped curvilinear relationship, but not linear association, was observed between citrus juice consumption and melanoma risk. Conclusions Citrus consumption was generally associated with a greater risk of malignant melanoma. Our findings may have important public health implications with respect to preventing melanoma.